Base promoted gem-difluoroolefination of alkyl triflones. Issue 39 (16th April 2021) - Yang, Ren-Yin; Wang, Hui; Xu, Bo
Abstract : A new synthesis of gem -difluoroalkenes from readily available alkyl triflones and difluorocarbene precursors such as TMSCF2 Br has been reported. Abstract : A new synthesis of gem -difluoroalkenes from readily available alkyl triflones and difluorocarbene precursors such as TMSCF2 Br has been reported. The reaction, regardless of electronic effect, gives gem -difluoroalkenes in good to excellent yields. The mechanism may involve deprotonation of triflones, nucleophilic addition, and the elimination of SO2 CF3 .